(untitled) (International Journal of Language, Literacy and Translation, 2025)
Vocabulary is a crucial aspect of language acquisition and plays a vital role in dictating learners’ proficiency level at different ages. A key aspect of second language acquisition (SLA) is the development of a broad vocabulary. This review looks at how learners approach vocabulary learning, different categories of vocabulary, and the main objectives of vocabulary acquisition. The paper additionally explores Vocabulary Learning Strategies and how they affect vocabulary development in SLA. Cognitive tactics, including memorising techniques or metacognitive strategies, which entail learners reflecting on their learning process and tracking their progress, may be used to approach vocabulary acquisition. Working with peers or teachers to acquire vocabulary is another efficient approach to using social learning tactics. Learners must have word knowledge, which encompasses academic, domain-specific, colloquial, technical, and idiomatic vocabulary, in addition to expressive and productive vocabulary, to improve their vocabulary acquisition. Additionally, grammatical complexity greatly influences word acquisition, and modern learning tools like social media apps, subtitles, and short tales provide new approaches to enhancing vocabulary learning. In summary, effective Vocabulary Learning Strategies (VLS) are crucial in SLA, and learners should use various strategies to pick up a wide variety of vocabulary. When creating language teaching programmes, language teachers should also consider each learner’s requirements and motivations. Utilising fresh learning resources and media may provide learners with more options for enhancing their vocabulary learning and enhancing their overall language skills.